Socio-Economic Development of Transportation in Fufore, Nigeria - Ahmed Belel, Zaheeda; Ahmed Belel, Waheeda; Abubakar, Mahmoud Hijab; Belel Ahmed, Zainab; Daud, Zawawi; Awang, Halizah (International Journal of Integrated Engineering, 2018)
Transportation is a critical factor in the economic growth and development. Inadequate transport system limits a nations ability to utilize its natural resources, distribute goods and other finished goods. Hence transportation is the most bases for economic growth and development in most societies. This study examines the Impact of Transportation on Economic Development of Fufore Local Government Area of Adamawa State. The study covered five villages which were selected using multistage sampling technique. About 105 respondents were also selected and administered a set of questionnaires using random method. Descriptive statistics were used foe analysis of data gathered. The findings of the analysis revealed that 44.79% of the respondents are farmers. It also shows that the most common means of transportation in the study area is motorcycle and lack of good roads makes it difficult for the respondents to access good markets for their farm produce as more than 65.63% of roads in the area are in bad condition which leads to rise in cost of transportation. This was discovered to have affected the economic activities of the people thereby increasing the level of poverty in communities in the study area.Â The construction of new roads and maintenance of existing ones is therefore recommended to reduce cost of transportation of goods and services thereby reducing poverty and boosting economic growth and development.